Synthesis of Novel Glutamate-Zinc-Aluminium-Layered Double Hydroxide Nanobiocomposites - Md. Ajat, Mohd Mokrish (2006)
Nanobiotechnology at present is very much important, especially for catalysis, composite applications and for the development of delivery vector for beneficial agents. A compound of zinc-aluminium layered double hydroxides (LDH) to be used as a host for a guest amino acid, glutamate was synthesized using direct assembly or co-precipitation method. Different parameters were used and optimized to form amino acid-intercalated pure phase materials. Two Bio-Inorganic Nanohybrid (BINH) were chosen for further characterization and showed that one of them had a dimer molecule intercalated into the interlayer region. Both BINHs exhibits the glutamate to be in vertical or perpendicular orientation to the inorganic layers. Cytotoxicty test indicated that the cells were insusceptible to the LDH synthesized at ratio (Zn/Al) = 1. Results from this study will be used in the development of a new delivery system for therapeutic agents comprising amino acids or peptides.